FAKTOR YANG BERPERAN TERHADAP KEAKTIFAN KADER KESEHATAN DALAM PENEMUAN KASUS TERDUGA PENDERITA TB PARU - Rosinta MM Hutabarat; Achmad Rifai; Tengku Moriza (Jurnal Keperawatan Priority, 2022)
The eradication of pulmonary TB in Indonesia is one of the national priorities for the tuberculosis disease. The purpose of the study was to analyze the factors that influence the activity of health cadres in finding suspected cases of pulmonary TB patients in the working area of ​​Siatas Barita Health Center, North Tapanuli Regency. The design of this research was an analytic survey with a cross-sectional design. This research was conducted in the Working Area of the Puskesmas Siatas Barita, North Tapanuli Regency from Mei to Juni 2021 with a sample of 80 people. Data analysis was carried out by univariate, bivariate, and multivariate analysis. The statistical test used is the chi-square test and logistic regression. The results of the chi-square test showed that the variables of knowledge, attitude, motivation, and monitoring p-value = 0.000 < 0.05, meaning that there was an influence between knowledge, attitude, motivation, and supervision of cadre activity. influential in this study is the motivation variable. The conclusion was that there is an intermediate influence. there was an influence between knowledge, attitude, motivation, and supervision on cadre activity, while multivariate analysis shows that the most dominant factor was the motivation variable on cadre activity. It was recommended to the District Health Office to increase the frequency of supervision and monitoring of the implementation of the pulmonary TB control program in the puskesmas area, specifically the active and sustainable health cadres.